Statistical estimates of the catastrophes frequency - Касьянов, В.О.; Гончаренко, А.В. (Proceedings of National Aviation University (archive), 2004)
Statistical material on aviation catastrophes for over a 30-year period has been processed. The character of the catastrophic events flow frequency dependence upon the maintenance, overhaul, and repair costs has been proved. Statistical data of flight safety indexes are adduced.